The effect of supercapacitors in a tidal current conversion system using a torque pulsation mitigation strategy. (February 2019) - Sousounis, Marios Charilaos; Shek, Jonathan K.H.; Sellar, Brian G.
Highlights: Full resource-to-grid modelling of a tidal current conversion system with a supercapacitor module connected at the DC link. Analysis and performance of a torque pulsation mitigation strategy for fatigue loads with and without supercapacitors. Study of regulating the DC link voltage spikes with supercapacitors and its effect on grid integration for a tidal system. Show the importance of connecting voltage regulating supercapacitors in a tidal current array concept. Abstract: The research presented in this paper investigates the effect of connecting supercapacitors at the DC link of a hypothetical 1.5 MW three-bladed variable-pitch horizontal-axis tidal current turbine that uses a torque pulsation mitigation strategy. Torque pulsations are classified into fatigue torque and ultimate or peak torque. Both can lead to premature components failure or system overdesign and costly maintenance. Research has suggested that torque pulsations can be mitigated by using a novel control strategy with which pulsations created by the unsteady tidal current flow are reduced by changing the generator speed. Increasing the variation of the generator speed increases the variation of the electrical power output of the generator. The electrical power output of the generator is injected to the grid through back-to-back AC to DC, DC to AC converters. The increased variation of the electrical power output of the generator causes DC link voltage spikes, increases the stress of electrical components and affects the compliance of the tidal current conversion system for grid connection. In order to tackle these problems a supercapacitor module is proposed to be connected at the DC link. The supercapacitor is able to absorb the fast short-term variations of the electrical power and keep the DC link voltage within limits. The potential benefits of using supercapacitors for connection in weaker grids and in tidal current arrays are also studied. Results show that DC link voltage and grid side harmonics are positively affected from the installation of a supercapacitor at the DC link.